2020
DOI: 10.1186/s12891-020-03834-w
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an electronic care pathway for hip fracture patients: a pilot before and after study

Abstract: Background Care pathways are generally paper-based and can cause communication failures between multidisciplinary teams, potentially compromising the safety of the patient. Computerized care pathways may facilitate better communication between clinical teams. This study aimed to investigate whether an electronic care pathway (e-pathway) reduces delays in surgery and hospital length of stay compared to a traditional paper-based care pathway (control) in hip fracture patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…However, cardiac rehabilitation continues to have poor attendance rates, with only 15%–30% of eligible patients engaging with the programme 12,13 . To address poor uptake, policymakers and healthcare providers need to ensure that interventions are well‐accepted and adapted to the specific needs and perceptions of the target population 14,15 . One way to achieve this is for researchers to work with end‐users and nonacademic stakeholders in the development of interventions; this is known as co‐design.…”
Section: Introductionmentioning
confidence: 99%
“…However, cardiac rehabilitation continues to have poor attendance rates, with only 15%–30% of eligible patients engaging with the programme 12,13 . To address poor uptake, policymakers and healthcare providers need to ensure that interventions are well‐accepted and adapted to the specific needs and perceptions of the target population 14,15 . One way to achieve this is for researchers to work with end‐users and nonacademic stakeholders in the development of interventions; this is known as co‐design.…”
Section: Introductionmentioning
confidence: 99%
“…190 studies underwent full-text review, and 69 studies were selected for final analysis ( Figure and eAppendix 3 in the Supplement ). 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 …”
Section: Resultsmentioning
confidence: 99%
“…190 studies underwent full-text review, and 69 studies were selected for final analysis (Figure and eAppendix 3 in the Supplement). Among the final 69 improvement programs, 49 programs significantly decreased TTS 33,35,38,41,[43][44][45][46][47][48][49][51][52][53][54]56,57,[59][60][61][62][65][66][67][68][69][70][71][72][74][75][76][79][80][81][82][85][86][87][88]91,94,96,97,99,101,103 and 20 programs 39,40,42,50,…”
Section: Included Studiesmentioning
confidence: 99%
“…Patients with hip fracture had the highest rate of hospital admissions and subsequent admission to a rehabilitation ward, which contributed to the highest costs per patient. Clinical novel solutions to reduce hospital length of stay and associated in-hospital costs for hip fracture patients are warranted [ 29 ]. Admission rates to a RAC facility were low across non-hip fracture groups, similar to results from a recent cohort study that reported risk of institutionalization 6 months after multiple fracture sites compared to hip fractures [ 30 ].…”
Section: Discussionmentioning
confidence: 99%